Brief communication; "The integration of remote sensing and meteorological data for monitoring irrigation demand in Cyprus" - Papadavid, George; Agapiou, Athos; Michaelides, Silas; Hadjimitsis, Diofantos G. (My University, 2009)
This paper examines and evaluates the integrated use of satellite remote sensing and meteorological data for estimating crop water requirements over agricultural areas of Cyprus. Intended purpose of this project is to estimate evap- otranspiration using modeling techniques, satellite and meteorological data for monitoring irrigation demand. ETc was calculated with the FAO Penman-Monteith method by using satellite images acquired from July to December 2008. ETc estimates obtained in this project were compared to previous empirical data found by using in-situ techniques. ETc values have been correlated with the meteorological data to crosscheck the significance of the meteorological inputs.
Keywords: Evapotranspiration; Energy balance; Evaporative fraction